2023
DOI: 10.3390/su152115625
|View full text |Cite
|
Sign up to set email alerts
|

Viability of Living Moss for Indoor Green Walls: A Study on Temperature, Humidity, and Irrigation

Harald G. Zechmeister,
Leonie Möslinger,
Azra Korjenic
et al.

Abstract: There is an increasing demand for green plant walls in indoor environments because of their multifaced benefits, such as aesthetic appeal, indoor air quality improvement, or psychological well-being. Mosses are believed to be excellent for these walls due to their easy application and maintenance. However, so far there is no evidence for their indoor survival. In this study, we tested the moss species Hypnum cupressiforme, Bryachythecium rutabulum, Eurrhynchium angustirete, Thuidium tamariscinum, Streblotrichu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Typically, in the literature, we will encounter examples of short exposure times for samples, which is explained due to practical reasons (to keep the biomonitor's vitality, to record a shorttime, or to avoid accidental pollution) [39]. However, the vitality aspect is considered in a small number of papers [40,41], although the relevance of considering this parameter in biomonitoring and physiological studies has been demonstrated [42,43]. Nevertheless, a considerable number of studies use devitalized material [44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…Typically, in the literature, we will encounter examples of short exposure times for samples, which is explained due to practical reasons (to keep the biomonitor's vitality, to record a shorttime, or to avoid accidental pollution) [39]. However, the vitality aspect is considered in a small number of papers [40,41], although the relevance of considering this parameter in biomonitoring and physiological studies has been demonstrated [42,43]. Nevertheless, a considerable number of studies use devitalized material [44][45][46].…”
Section: Introductionmentioning
confidence: 99%